Politik Konservasi Taman Nasional Batang Gadis Kabupaten Mandailing Natal - SAPUTRA, DONY; SOETARTO, ENDRIATMO; ADIWIBOWO, SOERYO (Politeia: Jurnal Ilmu Politik, 2014)
Conflict is a part of social phenomenon. The conservation policy of Batang Gadis National Park (TNBG) âat Mandailing Natal Regency Sumatera Utara Province- coloured with diverse interests of the actors. These interests had caused a conflict due to the overlap of area of TNBG and area of mining concession owned by PT. Sorikmas Mining (PT. SMM). This research pur-poses to explore and examine the interests behind establishment of conservation policy of TNBG which had emerged conflict from political eclogy perspective. The finding shows that establish-ment policy of TNBG was not purely initiated by environmental preservation motives, but TNBG was an existence of diverse economic interests of many actors. TNBG is also became arena by local elites and the NGO activist for their local political purposes. This study is using political ecology as the approach and the data collection is using field research. Analysis is using qualitative technique.Keywords: Conservation policy, political ecology, conflict.